Irish journalists and litterateurs in late Victorian London, c. 1870-1910 - Sheehy, I; Sheehy, Ian (2003)
﻿ This thesis is an exploration of Irish literary emigration to London in the nineteenth century, with particular reference to the 1880s and 1890s. These two decades witnessed a conflict between two generations of Irish emigrant writers and it is this conflict which forms the basis of the thesis. On the one hand were those emigrants - T.P. O'Connor, Justin McCarthy and R. Barry O'Brien - who typified the Irish literary defection to London in the nineteenth century, moving to England for a mixture of political, social, economic and cultural reasons. They were nationalists, but, like most Irish literary emigrants before them, they integrated themselves with British political and cultural life, developing a 'mixed' political-cultural identity in which British elements - principally Liberalism - were at play as well as Irish ones. By the 1880s they were well established in the world of Liberal London and played a prominent role in the Liberal Home Rule campaign of 1886-92. In these years, however, a new generation of Irish literary emigrants arrived in London - men like W.P. Ryan and D.P. Moran - and they were to be influenced by the Irish cultural revival rather than British Liberalism, becoming involved in the Southwark Irish Literary Club, the Irish Literary Society and the London Gaelic League during the 1880s and 1890s. Coming into contact with the 'Home Rule' writers, this 'Revival' generation would see their forerunners, with their 'mixed' identities, as Irishmen who had compromised culturally, who were essentially Anglicised. These cultural 'warnings' helped stimulate the cultural nationalism of the younger men, who, in the early 1900s, rejected the example of the 'Home Rule' generation and the longstanding pattern of cultural assimilation that they represented, by returning to Ireland and working for the Gaelic revival there. In doing so they illustrated the contrasting ways in which emigration to London could affect Irish litterateurs in the late nineteenth century.